Complex Modeling and Adaptive Sliding Control Law for Mars Airplane. Issue 2 (June 2014) - Liu, Yanbin; Yang, Chaoxing; Lu, Yuping
The application of an airplane to explore Mars may become an important research aera due to some distinctive advantages such as the large detection range and good maneuvering characteristics. Also, the resulting works have the strong forward-looking and driving actions which are helpful for mankind to realize the intergrated design dreams concerning aerospace technologies. This paper discusses the complex modeling and sliding control law design issues for Mars airplane. First, the particular features with regard to atmospheric environment on Mars are considered to explain the Martian flight principles as well as to provide the faced new challeges in comparison to the conventional airpalne on Earth. Afterwards, the mathematical model of Mars airplane is established using the isolation methods, and based on this built model the dynamic characteratics are analyzed under the Martian atmospheric environment in order to indicate the importance of the control actions. Furthermore, the sliding control law is proposed to meet the anticipated demands including robust stability and adaptive track response. Finally, a simulation example is given to verify the effectiveness of the proposed modeling and control methods, and the according works will also provide the good theoretical reserve and technical support to independently develop Mars airplane in the future.